(untitled) (International Journal of Environmental Sciences, 2025)
This study investigated the disaster risk management (DRM) strategies and the indigenous practices in Barangay Pinsao Proper, Baguio City, hypothesizing that their combination enhances community resilience. Using an explanatory sequential mixed-method approach, the research gathered data from 301 residents through surveys and qualitative interviews with local leaders and residents of the barangay. Findings indicate moderate DRM awareness but highlight deficiencies in evacuation protocols, land use planning, and vulnerability assessments. Traditional practices such as bayanihan (communal unity), binnadang (mutual aid), and ritual-based disaster predictions remain vital components of local resilience. These practices, deeply embedded in the community’s culture, complement scientific DRM approaches by fostering collective action and environmental awareness. The study emphasized the need for DRM programs that integrate indigenous knowledge with modern frameworks to improve preparedness and response. To bridge existing gaps, structured educational initiatives, policy support, and multi-sector collaboration are essential. Recognizing indigenous knowledge strengthens community ownership of DRM strategies and promotes sustainable, culturally responsive disaster preparedness. This research underscores that effective DRM extends beyond technical expertise, relying on social cohesion, cultural values, and shared responsibility among government agencies, academic institutions, and local communities.